The contribution of the regional child protection commission of Bangka Belitung in dealing with children victims of sexual violence - Karim, Sahrul; Lessy, Zulkipli (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
Over the last two decades, the government has paid much more attention through imposing laws to minimize sexual violence against children. This mostly has been perpetrated by people close to them or extended family members. Accordingly, detrimental effects of such an immoral act case lead to physical problem and psychological disorder in children. Many cases are just the tip of the iceberg whereby disclosure has not been made because perpetrators fully know victims who always face threat in their lives. The interview was conducted with three counselors and key person or supervisor in the Regional Child Protection Commission (KPAD) to raise a concern about victims and to investigate the contribution of the KPAD in dealing with children victims of sexual violence. This study is undertaken as a result of the phenomena of sexual violence occurring in the Bangka Belitung Islands Province. Field research with qualitative descriptive-analysis method was employed in this study, and technique for data analysis applied a model of Miles et al. (2014). The findings showed that the contribution of KPAD in handling with victims of sexual violence against children includes providing assistance and advocacy, recovering trauma, boosting motivation, offering counseling, and giving assistance for legal justice technically and substantively. With the treatment, the KPAD of the Bangka Belitung Islands Province also provide the opportunity to assist the provincial government in facilitating the needs of the community who are able to contribute considerably to deal with the issues of sexual violence against children.